Challenges in the management of asthma associated with smoking-induced airway diseases. (22nd September 2018) - Thomson, Neil C
ABSTRACT: Introduction : Smoking-induced airway diseases such as chronic bronchitis, emphysema, and small airway dysfunction contribute to the chronic respiratory symptoms experienced by adults with asthma, including those with spirometric chronic obstructive pulmonary disease (COPD), termed asthma-COPD overlap (ACO). Drug treatment of symptomatic smokers with asthma or ACO is uncertain due to their exclusion from most clinical trials. Areas covered : This review summarizes evidence for the efficacy of small molecule drugs used in the clinic to treat current and former smokers with a diagnostic label of asthma or ACO. Other therapeutic interventions are reviewed, including smoking cessation and biologics. Expert opinion : Clinical trials and observational studies suggest that smoking cessation and approved drugs used to treat non-smokers with asthma produce clinical benefits in smokers with asthma or ACO, although the overall quality of evidence is low. The efficacy of some treatments for asthma is altered in current smokers, including reduced responsiveness to short-term inhaled corticosteroids and possibly improved responsiveness to leukotriene receptor antagonists. Preliminary findings suggest that low-dose theophylline, statins, and biologics, such as omalizumab, mepolizumab, and dupilumab, may improve clinical outcomes in smokers with asthma or ACO. Improved phenotyping and endotyping of asthma and smoking-induced airway diseases should lead to better targeted therapies.